Targeting Clostridium difficile Surface Components to Develop Immunotherapeutic Strategies Against Clostridium difficile Infection - Péchiné, Séverine; Bruxelle, Jean F.; Janoir, Claire; Collignon, Anne (Frontiers in Microbiology, 2018)
New therapies are needed to prevent and treat Clostridium difficile infection and to limit the rise in antibiotic resistance. Besides toxins, several surface components have been characterized as colonization factors and have been shown as immunogenic. This review will focus on passive and active immunization strategies targeting C. difficile surface components to combat C. difficile. Concerning passive immunization, the first strategies used antisera raised against the entire bacterium to prevent infection in the hamster model. Then, surface components such as the flagellin and the S-layer proteins were used for immunization and the passive transfer of antibodies was protective in animal models. Passive immunotherapy with polyvalent immunoglobulins was used in humans and bovine immunoglobulin concentrates were evaluated in clinical trials. Concerning active immunization, vaccine assays targeting surface components were tested mainly in animal models, mouse models of colonization and hamster models of infection. Bacterial extracts, spore proteins and surface components of vegetative cells such as cell wall proteins, flagellar proteins and polysaccharides were used as vaccine targets. Vaccine assays were performed by parenteral and mucosal routes of immunization. Both gave promising results and pave the way to development of new vaccines.